The Relationship between the Frequency of Formula Feeding and the Use of Milk Bottle Size with the Nutritional Status of Infants Aged 0-24 Months at Puskesmas Merdeka, Bogor City: Hubungan Frekuensi Pemberian Susu Formula dan Penggunaan Ukuran Botol Susu dengan Status Gizi Bayi Usia 0-24 Bulan di Puskesmas Merdeka, Kota Bogor - Anwar, Khoirul; Salsabilla, Alya; Syah, Muh. Nur Hasan (Universitas Airlangga, 2023)
Background: An infant (aged 0-24 months) is in a growth phase prone to nutritional problems if the infant's food intake is improper. Based on the data in Bogor City, the number of babies exclusively breastfed in 2020 was only 54.7%. A 100 ml formula milk has energy and protein contents of 10-18% and 55-80%, respectively, higher than breast milk, causing infant obesity. Objectives: Analyze the relationship between the frequency formula consumption and use bottle size with the nutritional status of infants aged 0-24 months. Methods: The study was conducted quantitatively (descriptive) with a Cross-Sectional Study design with mothers of children aged 0-24 months as willing and active respondents coming to posyandul. Respondents amounted to 66 people who were divided into groups with different formula milk frequencies: 1-4 bottles and > four bottles per day and use â‰¤180 ml and >180 ml bottle sizes per day. Respondents were selected by purposive sampling. The statistical test uses Mann withney for the difference test and Spearman rank for the relationship test. Results: There was a significant relationship between the frequency of formula feeding and the growth index of WHZ (P=0.005; R=0.338). There was a significant relationship between the use of formula bottle size and HAZ growth index (P=0.021; R=0.283), WHZ (P=0.023; R=0.280), and BAZ (P=0.004; R=0.353). Conclusions: There are differences in nutritional status in using milk bottle sizes. Nutritional Status Infants with WHZ growth index showed significant results leading to obesity in infants given formula milk >4 bottles per day.